DNA methylation, a hand behind neurodegenerative diseases - Lu, Haoyang; Liu, Xinzhou; Deng, Yulin; Qing, Hong (Frontiers in Aging Neuroscience, 2013)
Epigenetic alterations represent a sort of functional modifications related to the genome that are not responsible for changes in the nucleotide sequence. DNA methylation is one of such epigenetic modifications that are intensively studied during several decades. The transfer of a methyl group to the 5 position of a cytosine is the key feature of DNA methylation. Such a change, though simple, can be caused by various kinds of factors, and also can affect a large number of severe diseases, including neurodegenerative diseases. In this review, we retrospect and summarize recent progress about DNA methylation in four major neurodegenerative diseases, i.e. Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis. These studies together strongly suggest an important role of DNA methylation in neurodegenerative diseases. However, some areas of each disease still remain unclear and further tests are necessary. We hope this review can provide a new insight into understanding neurodegenerative diseases in an epigenetic way.